Genetic and clinical characterization of congenital fibrinogen disorders in Polish patients: Identification of three novel fibrinogen gamma chain mutations. Issue 182 (October 2019) - Wypasek, Ewa; Klukowska, Anna; Zdziarska, Joanna; Zawilska, Krystyna; Treliński, Jacek; Iwaniec, Teresa; Mital, Andrzej; Pietrys, Danuta; Sydor, Wojciech; Neerman-Arbez, Marguerite; Undas, Anetta
Abstract: Introduction: Congenital fibrinogen disorders are poorly explored in Slavic populations. The aim of this study was to characterize the genetic background and clinical manifestations of fibrinogen disorders in the Polish case series. Materials and methods: In 27 unrelated patients (mean [SD] age, 30.4 [19.2] years, 30% men) with fibrinogen concentration (von Clauss method) < 1.8 g/L, exons and intron-exon junctions of the fibrinogen alpha chain ( FGA ), fibrinogen beta chain ( FGB ), and fibrinogen gamma chain ( FGG ) genes were analyzed using polymerase chain reaction (PCR) amplification followed by sequencing. Results: At enrollment, 15 (55.6%) and 2 (7.4%) of patients experienced bleeding and thrombotic events, respectively, and the remainder were asymptomatic. The following congenital fibrinogen disorders were identified: 1A. afibrinogenemia, n = 1; 2A. severe hypofibrinogenemia, n = 2; 2B. moderate hypofibrinogenemia, n = 4; 2C. mild hypofibrinogenemia, n = 6; 3A. dysfibrinogenemia, n = 12; 3B. thrombotic related-dysfibrinogenemia, n = 1; 4C. mild hypodysfibrinogenemia, n = 1. Eight dysfibrinogenemic patients (62%) were carriers of hotspot mutations. Fifteen patients were heterozygous and one (afibrinogenemia) homozygous for known causative mutations. Three new heterozygous mutations were detected, all affecting splicing in FGG : fibrinogen Poznan II, a 177 bp deletion eliminating parts of intron 6 and exon 7 in a dysfibrinogenemic woman with recurrent bleeding; fibrinogen Zakopane, (intron 2 acceptor splice site) and fibrinogen Belchatow (intron 1 donor splice site), found in hypofibrinogenemic patients. During follow-up (median 60, interquartile range 10–60 months), bleeding episodes, mainly menorrhagia and easy bruising were reported in 15 (55.6%) patients. One thromboembolic event was observed. Conclusion: This study of the largest cohort of Slavic patients with congenital fibrinogen disorders has enabled the identification of 3 new FGG mutations and shows a high prevalence of bleeding manifestations with recurrences. Highlights: Congenital fibrinogen disorders are poorly explored in Slavic populations Three new mutations affecting splicing were detected in FGG gene: fibrinogen Poznan II, fibrinogen Zakopane and fibrinogen Belchatow Like in other populations, hotspot mutations linked to dysfibrinogenemia were observed in most patients During a five-year follow up bleeding episodes, mainly menorrhagia and easy bruising were reported in 55% patients